Current situation of Helicobacter pylori infection in Indonesia (Faculty of Medicine Universitas Indonesia, 2016)
The epidemiology of Helicobacter pylori (H. pylori) has been changing over the past decades. Indonesia was reported have a low prevalence of H. pylori infection compared to other countries in Asia. Some studies in Indonesia have evaluated that poor sanitation, age, religion, ethnicity are the risk factors for H. pylori infection. Compared to other diagnostic tests, the urine test will be reliable for the detection of H. pylori in Indonesia because it is non-invasive and low cost with high accuracy. Although we have already performed studies on the prevalence of H. pylori infection in several ethnics, we still have some questions that remain unclear regarding H. pylori infection in Indonesia. Therefore, we have a need to build a H. pylori center that provide facilities for culturing, evaluating antibiotic resistance, and obtaining the genotype information that may explain the differences in H. pylori infection among ethnic groups in Indonesia.